Digital Leadership and IT Strategy Execution in Emerging Economies - Angellia, Filda (Data : Journal of Information Systems and Management, 2024)
Digital transformation has emerged as a critical driver for organizational success in today’s rapidly evolving technological landscape. This narrative review aims to explore how IT strategy is formulated and implemented in digital enterprises, particularly within developing countries. Using a systematic literature search across Scopus, IEEE Xplore, and Google Scholar, studies were selected based on thematic relevance, quality, and citation impact. Keywords included "IT strategy formulation," "digital transformation," and "strategy implementation," combined through Boolean operators to refine search results. The review reveals that strategic frameworks such as the Ward and Peppard model and SECI model facilitate alignment between IT and business objectives. Internal organizational factors—notably leadership, culture, and technological readiness—play a pivotal role in enabling successful strategy formulation. Externally, government policies, infrastructure availability, and stakeholder influence significantly shape implementation outcomes. Agile methodologies, data-driven decision-making, and collaborative leadership emerged as critical practices in digital strategy execution. Conversely, barriers such as resistance to change, regulatory inertia, and limited digital competencies hinder progress, particularly in SMEs and public institutions. This review highlights the need for integrative and adaptive strategies that account for socio-technical and contextual complexities. It underscores the importance of inclusive governance and policy alignment to support digital innovation. Future research should investigate underexplored regional and sectoral contexts to develop holistic frameworks that support sustainable digital transformation across diverse organizational landscapes